Prospective Teachers' Views and Metaphors about Scientists and Their Scientific Methods - AĞLARCI ÖZDEMİR, OYA (DERGIPARK AKAD, 2019)
The aim of this study is to determine the views of prospective science and chemistry teachers from different grade levels on the scientific methods of scientists. The research method is case study which is a qualitative research design. First grade (n=27, 16) and last grade (n=30, 27) prospective Science and Chemistry teachers participated in the present study. 4 different open-ended questions prepared by the researchers were used in order to gather the data. Content analysis was performed for the assessment of the research data. When the results are considered in general, the findings contain common themes and also some differences. Although the last grade participants presented more sophisticated views on the topic, they were weak at certain points such as the significance of imagination. For this reason, department courses should also include the themes of scientific literacy and the nature of science.
Keywords: Science; scientist; scientific research; metaphoric perception; prospective teacher; SCHOOL STUDENTS IMAGES; SCIENCE